SWCNTs Interaction with Dopamine and Serotonin Anticancer Through QM/MM Methods: A Drug Delivery Approaches - Saghayi Marouf, Nastaran (2021)
Objetive: Dopamine and Serotonin are the two important biological transmitters that have hormonal activities and responsible for happiness and felling well. The aim of this article was to study theoretically the structure features of Dopamine and Serotonin in the complex of single-walled carbon nanotube as a neurotransmitter. Material and Methods: The structure of Dopamine and Serotonin binding with SWCNT with four different diameters (7.0,7.5,7.7,10.0 nm) was studied by using molecular mechanic (MM) and quantum mechanic (QM). The remarkable energies including potential energy, total energy and kinetic energy in time of simulation 10 ns steps in two temperatures (298, 310 kelvin degree) were investigated by Monte Carlo method with opls force filed. NMR shielding tensor data by B3LYP level of theory with 6-31 G(d) as a basis set and semi empirical method have been also fulfilled. Results: Theoretical computations were performed to study NMR chemical shift data including magnetic shielding tensor (σ, ppm), shielding asymmetry (η), magnetic shielding anisotropy (σaniso), magnetic shielding isotropy (σiso) , skew of a tensor (Κ) and chemical shift anisotropy (Δσ) and span (Ω) at various rotation angles around a specific rotation, physical and chemical properties of atomic nuclei. Semi empirical calculations such as total energy, binding energy, isolated atomic energy, electronic energy, core–core interaction and heat of formation in AM1 were revealed. Conclusion: It is figured out in Monte Carlo method our two specific drug and its nanotube with small diameter are the most stable one than the others. The larger diameter leads the combination stability into lower value.